Quantum physics and theology : an unexpected kinship - Polkinghorne, John. C., 1930-2021 (New Haven ; London : Yale University Press, 2007)
The author identifies and explores key similarities in quantum physics and Christology. Among the many parallels he identifies are patterns of historical development in quantum physics and in Christology; wrestling with perplexities such as quantum interpretation and the problem of evil; and the drive for an overarching view in the Grand Unified Theories of physics and in Trinitarian theology. Both theology and science are propelled by a desire to understand the world through experienced reality, and Polkinghorne explains that their viewpoints are by no means mutually exclusive. --from publisher description
The search for truth -- Comparative heuristics -- Lessons from history -- Conceptual exploration -- Cousins
Includes bibliographical references and index
Keywords: Religion and science; Quantum theory; Theology